Tilak’s Inclusive Cultural Nationalism: A Critical Reassessment from an Indian Perspective - Abulkod, Mukul Potanna (International Journal of Research in Interdisciplinary Studies, 2025)
This study revisits Bal Gangadhar Tilak’s writings to explore his conceptualization of inclusive cultural nationalism—a vision that integrates India’s diverse religious and cultural traditions. By conducting a close reading of authenticated primary and secondary and contrasting these findings with prevailing Western-centric narratives, the research identifies significant gaps in prevalent research. The project aims to enrich the discourse on nationalism by foregrounding the cultural dimensions that have been historically underexamined. The study identifies subaltern perspective of Tilaks nationalism and shoe how he wasn’t as conservative as its thought of him in the recent contemporary history. It studies how he gave paramount importance to political reform (Swaraj) but was also liberal in social and economic reforms which includes empowerment of all marginalised and alienated groups like women, traders, labourers, farmers and most importantly Muslim and Dalits.